Sympolymnia, a new genus of Neotropical ant-like spider, with description of two new species and indirect evidence for transformational mimicry (Araneae, Salticidae, Simonellini) - Perger, Robert (2020)
Sympolymnia, a new genus of myrmecomorph jumping spider belonging to the tribe Simonellini Peckham, Peckham & Wheeler, 1889, is described. It comprises five species: the type species, Sympolymnia lucasi (Taczanowski, 1871), comb. nov., Sympolymnia lauretta (Peckham & Peckham, 1892), comb. nov., Sympolymnia edwardsi (Cutler, 1985), comb. nov. and Sympolymnia shinahota sp. nov. and S. cutleri sp. nov. Sympolymnia lauretta (Peckham & Peckham, 1892) is recorded from Bolivia for the first time. Ontogenetic shifts of ant-resemblance are observed: Juveniles of S. cutleri sp. nov. and S. lauretta mimic black ants of the genus Crematogaster Lund, 1831, but those of S. shinahota sp. nov. most closely resemble Pseudomyrmex ethicus (Forel, 1911). Adults of S. cutleri sp. nov., S. lauretta and S. shinahota sp. nov. resemble the ant Camponotus sanctaefidei Dalla Torre, 1892 and orange adults of S. shinahota sp. nov. are putative mimics of Camponotus latangulus Roger, 1863.